ENGINEERING CONTRIBUTION TO TECHNOLOGY OF BORING DRILLING OF MINING HOLES ON PRICARPATTI AFTER 1939 - Яремійчук, Роман Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We describe the development of well drilling techno-logies at Precarpathia in 1945-2000. We consider the drilling technologies, where the gas stream is given under pressure, the drilling of large diameter wells, the drilling of superdeep wells and drilling of complex profile wells.